Young Black Teachers Taking to Social Media to Shame Black Students and Parents: A Narrative Review - Benson, Keith E. (Advances in Social Sciences Research Journal, 2024)
Social media is a group of technologies that offers people avenues to engage with one another in a virtual and digital space through their computer or smartphone (Ober & Wildman, 2015) with young black Americans consuming social media more, proportionally, than any other demographic. As such, young Black educators are increasingly availing themselves to social media as a space to communicate and share their professional experiences with other black educators, and the world. In so doing, some young black educators opt to use their social media platform, and their institutional authority to shine a negative light on their black students and parents. In this narrative review, I explore social media consumption, shaming within the educational context, and black teachers as distinct from lower income black parents and students to argue that rather than using their positions as educators to protect their students and parents, young black teachers who have achieved middle-class status and use social media to display their professional frustrations with their black students and parents, only accomplishes the shaming of those with less power and agency - the very people black teachers traditionally protected from harm.